Kepemilikan Hak Atas Tanah Bagi Warga Negara Timor Leste Menurut Konstitusi Republik Demokratik Timor Leste Tahun 2002 - klaudio klaudio; I Made Suwitra (Jurnal Hukum Prasada, 2017)
ABSTRACT After the Referendum of 1999, ownership of land rights in East Timor is still complicated bringing about problems such as: 1) How is the ownership of land rights for the people of East Timor by the Constitution of the Democratic Republic of Timor-Leste in 2002, 2) How is the Timorese government's efforts to resolve housing land disputes left by the former inhabitants of East Timor in Timor Leste. The type of research is Normative Legal Research by using legislation, concepts, analytical, case, and comparative law approaches. Materials used are in the form of primary legal materials, secondary, tertiary, and then analyzed by interpretation technic. The study found that land rights for the people of East Timor by the Constitution of 2002 was still weak. On the basis of Article 13 and 15 of Law No. 1 of 2003 on assets and immovable possessions the property rights on land owned by the ex-East Timorese people are automatically revoked or missing. Recommendation to the government of Timor Leste is that UUPA ever prevail in Timor-Leste can be adopted for under article 3, paragraph 1 of UNTAET Regulation No. 1 of 1999, land owned by the former inhabitants of East Timor adopted by some natives of East Timor must be reprocessed by the government of Timor Leste in accordance with the applicable law. Keywords: Land Ownership Rights, Residents of East Timor, The Constitution of 2002, The Housing Land Dispute.